The Influence of Internal Control and Organizational Culture on Fraud Prevention: A Systematic Literature Review - Olivia Putri Zahrani; Rela Sari (Pusat Penelitian dan Pengabdian Masyarakat (P3M) IBK Nitro, 2026)
This study analyzes the influence of internal control and organizational culture on fraud prevention using a Systematic Literature Review (SLR) of 20 indexed journal articles published between 2011 and 2026. From the perspective of Agency Theory, internal control functions to reduce information asymmetry between principals and agents, thereby lowering the likelihood of fraud. Meanwhile, organizational culture acts as a bonding mechanism that voluntarily aligns the interests of agents with those of principals. The findings indicate that strong internal control and an adaptive organizational culture positively enhance the effectiveness of fraud prevention. In contrast, a non-adaptive culture increases the risk of fraud and undermines organizational stability. This study recommends integrating formal controls with organizational culture to develop a comprehensive fraud prevention system.